Interfirm competition, intrafirm cannibalisation and product exit in the market for computer hard disk drives - Ruebeck, Christopher S. (Economic & Social Studies, 2002)
Intrafirm ?cannibalisation? of a product?s demand by the firm?s own products is found to have a more robust and significant relationship to the probability of its withdrawal than does interfirm competition from other firms? products.
Keywords: Competition; Product exit; Hard disk drives; Product differentiation